A Nearly Packaging‐Free Design Paradigm for Light, Powerful, and Energy‐Dense Primary Microbatteries (Adv. Mater. 35/2021). Issue 35 (2nd September 2021) - Yue, Xiujun; Johnson, Alissa C.; Kim, Sungbong; Kohlmeyer, Ryan R.; Patra, Arghya; Grzyb, Jessica; Padmanabha, Akaash; Wang, Min; Jiang, Zhimin; Sun, Pengcheng; Kiggins, Chadd T.; Ates, Mehmet N.; et al.
Abstract : Microbatteries The proliferation and performance of physically small electronics have been severely limited by the microbatteries that power them. In article number 2101760, John B. Cook, Paul V. Braun, James H. Pikul, and co‐workers report a new design paradigm for primary microbatteries that drastically improves energy and power density through the use of thick and near‐fully dense electrodeposited cathodes and multifunctional current collectors that eliminate most of the hermetic packaging.